1968
DOI: 10.1002/bjs.1800550511
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative intestinal motility an experimental study on dogs

Abstract: MAYleft-sided predominance of iliofemoral venous thrombosis and of post-thrombotic stricture formation. SUlMlMARYThe gross anatomy of the inferior vena caval bifurcation has been studied by dissection, corrosion cast preparation, and phlebography.Results have shown that :-I . T h e right common iliac artery crossed the junction of the left and right common iliac veins in 73 of 93 dissections.2. Compression of the left common iliac vein where it is crossed by the right common iliac artery was present in 29 of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 8 publications
0
6
0
4
Order By: Relevance
“…Opinions differ as to how long changes in myoelectrical activity persist after laparotomy and abdominal surgery. Some investigators have concluded that early postoperative intestinal motility and myoelectrical activity are normal in dogs (Baker andWebster 1968, Carmichael andothers 1977); others disagree (Smith and others 1977, Bueno and others 1978, Morris and others 1983.…”
Section: Introductionmentioning
confidence: 99%
“…Opinions differ as to how long changes in myoelectrical activity persist after laparotomy and abdominal surgery. Some investigators have concluded that early postoperative intestinal motility and myoelectrical activity are normal in dogs (Baker andWebster 1968, Carmichael andothers 1977); others disagree (Smith and others 1977, Bueno and others 1978, Morris and others 1983.…”
Section: Introductionmentioning
confidence: 99%
“…Others also described augmented periods, but the disordered contractile activity directly after surgery was followed by a period of quiescence (Baker and Webster, 1968). In the pig, a normal MMC length consists of 70-115 min (Rayner and Wenham, 1986), while only few data describe the immediate effects of surgery on duodenal motility.…”
Section: Discussionmentioning
confidence: 99%
“…Несоответствие ширины просветов функционирующей и отключённой частей подвздошной кишок на фоне развития отёка в зоне кишечного шва приводят к образованию временного механического препятствия в зоне анастомоза. Другой причиной нарушений проходимости кишечника после закрытия петлевой илеостомы следует считать ПП ЖКТ, представляющий собой одну из главных проблем в хирургии, частота развития которого составляет 3-17% [3,5,9,12,14,16,17,19,[21][22][23]27,28,[30][31][32]55]. В основе патогенетического механизма развития ПП ЖКТ лежит множество факторов, среди которых основными являются: операционная травма, нарушение гуморальной регуляции кишечника, угнетение спинномозговых рефлексов, повышенная активность симпатической иннервации, назначение опиоидных препаратов, которые воздействуют на одноименные рецепторы, а также нарушения водно-электролитного и белкового балансов.…”
Section: осложнения при ликвидации петлевой илеостомыunclassified